Análisis de la figura jurídica del nepotismo y sus efectos en la administración pública. - Pazmiño Pacheco, Eduardo Santiago (2013)
The present investigation work has as purpose, to propose a juridical instrument that regulates in a better way the mechanisms of control of Nepotism in the Public Administration whose purpose is to guide to the public officials of popular election or appointment, students and citizenship in general and to avoid the Nepotism especially in the Function Publishes. For it was necessary to carry out the fieldwork, by means of the type of descriptive investigation that allowed to describe in an exact way in the activities that are developed inside the public function, applying the observation and the surveys to Lawyers, Officials of the Controllership, obtaining good results to develop a feasible proposal.